Thickness-designable acoustic metamaterial for passive phased arrays. (September 2022) - Li, Lianchun; Diao, Yifan; Wu, Haijun; Jiang, Weikang
Graphical abstract: Highlights: Designable metascreen with adjustable thickness. Thin compared to conventional structures. Achieves impedance matching to cancel out the energy depletion impact of aberrant layers. Abstract: Passive phase-controlled acoustic arrays based on metamaterial surfaces artificially manipulate acoustic waves, which can be used in biomedical imaging and nondestructive testing. One of the most representative applications is ultrasonic therapy using a passive phased array within a complete 2 π phase. In contrast, the surface thickness is 1/10 the wavelength of the operating frequency. However, conventional design methods feature a fixed array thickness for a specific frequency. This becomes necessary for different application scenarios where different thicknesses are needed. This study proposed a labyrinth resonant cavity metascreen phased array based on Helmholtz resonators and convoluted labyrinth acoustic metamaterials. The thickness of this array can be optimized to accommodate a specific operating frequency to achieve full 2 π phase control by adjusting only one parameter. Theoretical simulations and experimental results verified the acoustic wave manipulation effect. The proposed method may find utility in applications for noninvasive ultrasonic therapy, including nondestructive testing, acoustic communication, and biomedical imaging.